Application of response surface methodology (RSM) for experimental optimization in biogenic silica extraction from rice husk and straw ash - Yigezu Temesgen Zewide; Temesgen Atnafu Yemata; Adane Adugna Ayalew; Hawi Jihad Kedir; Asab Alemneh Tadesse; Asmarech Yeshaneh Fekad; Alemayehu Keflu Shibesh; Fentahun Adamu Getie; Tegen Dagnew Tessema; Tessera Alemneh Wubieneh; Wondmagegn Wonago Kululo; Muluken Tilahun Mihiret (Scientific Reports)
Abstract This work aimed to extract silica from combination of rice husk (RH and Rice straw (RS) by optimizing the ash digesting process parameters with the aid of response surface methodology (RSM). The effects of three independent ash digestion process factors like sodium hydroxide concentration (1–3 M), temperature (60–120 °C) and time (1–3 h), for silica production from the mixture of rice husk (RH) and rice straw (RS) were studied. A quadratic model was used to correlate the interaction effects of the independent variables for maximum silica production at the optimum process parameters by employing central composite design (CCD) with RSM. The work indicates that the temperature is the most significant parameter among the model terms, followed by NaOH concentration, then time for digestion of ash for silica production. It may be because of the larger F-value for temperature, which influences to high extent of ash digestion for silica production. The proximate analysis discovered that RH/RS possessed compositions of high ash, volatile matter and fixed carbon content whereas low moisture content, i.e., 20.5 ± 0.46, 67.1 ± 0.78, 15.8 ± 0.35 and, 6.6 ± 0.37 wt.%, correspondingly. The characterization of RH/RS and silica were performed by employing thermogravimetric (TG) and differential thermal (DT), Fourier transforms infrared spectroscopy (FTIR), X-ray fluorescence spectroscopy (XRF) and Brunner–Emmet–Teller (BET) for confirmation of the silica production. Hence, this current study concludes that silica materials obtained from RH/RS (with purity > 97.35 wt.%) may be new materials in the Si–C–O system that may be used in construction, ceramics and silica gel that helps to absorb moisture.